Identifying pedagogical intervention in MOOCs learning processes: a conversational agent proposal - Rossi, Diego; Ströele, Victor; Campos, Fernanda; Braga, Regina; David, José Maria N. (Anais do Simpósio Brasileiro de Informática na Educação (SBIE), 2021)
Monitoring students in virtual learning environments can be a time-consuming task. Professors and tutors must accompany students in an agile manner. During the COVID-19 pandemic, the use of discussion forums posed new challenges. This work proposes a conversational agent to automatically detect which pedagogical intervention is necessary to guide students in MOOCs environments. Through the attributes of the students' post messages, it is possible to classify which action will be carried out by the agent, applying specific dialogue patterns. In some more specific cases, the tutor's attention is immediately requested. The proposal was evaluated through a feasibility study to verify if semantic detection can contribute to guide the intervention process. According to the results, it is possible to support the tutor, as only 35.2% of interactions required the tutor's action.